Analysis of Social and Economic Aspects of MSMEs Kepang Geger in The Perspective of Sharia SKB - Kamelia Khasanah (Jurnal Impresi Indonesia, 2024)
MSMEs play an important role in reducing unemployment, alleviating poverty, and promoting economic growth. This study aims to assess the socioeconomic conditions of kue kepang business owners in Busela, Dabung, Geger, Bangkalan, Madura, and evaluate the feasibility of the business from a social and economic perspective. This qualitative research used in-depth interviews and observation to collect primary and secondary data directly from the business location. The data were analyzed descriptively to understand the socioeconomic phenomena related to the Kue Kepang business. The findings show that the Kue Kepang business significantly empowers the local community by providing jobs for 10-15 people. The business not only maintains and promotes local cultural heritage but also contributes to regional economic stability. The average monthly income of business owners ranges between IDR 5,587,714 and IDR 5,915,000, depending on whether they rent or own their business premises. However, the business faces risks such as fluctuating raw material prices and competition from similar products that need to be managed for sustainable growth. The study concludes that the Kue Kepang business is viable and beneficial from an economic and social perspective, contributing significantly to local community development and cultural preservation.